1982
DOI: 10.1001/archinte.142.13.2299
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aerosols II. Therapeutic aerosols

Abstract: The current uses of clinical aerosols such as water, saline, mucolytics, bronchodilators, cromolyn sodium, corticosteroids, and antimicrobials have been reviewed. The benefits of water, saline, and detergent aerosols continue to be surrounded by uncertainty and controversy. Aerosolized mucolytic and proteolytic agents have not been conclusively shown to be of substantial value in the improvement of respiratory disorders. Favorable bronchodilator therapy is achieved with aerosols of certain sympathomimetic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 135 publications
0
11
0
Order By: Relevance
“…In the past, the first therapeutic choice was to prescribe nasal washes to help mucus removal, associated to several drugs that were tested for their mucolytic properties. Many studies were performed giving disconcordant results; the only substance that showed significant effect on mucus reduction was N-Acetilcysteine (NAC) (8)(9)(10).…”
mentioning
confidence: 99%
“…In the past, the first therapeutic choice was to prescribe nasal washes to help mucus removal, associated to several drugs that were tested for their mucolytic properties. Many studies were performed giving disconcordant results; the only substance that showed significant effect on mucus reduction was N-Acetilcysteine (NAC) (8)(9)(10).…”
mentioning
confidence: 99%
“…The lungs with a combined surface area of more than 100 m together with a low metabolic activity (Lourenco andCotroman, 1982, Clarke andNewman, 1984) makes them an ideal site for drug absorption and a potential route for the systemic administration of certain drugs that cannot be delivered by other means. Many studies have shown that greater bioavailability has been achieved for macromolecular drugs than any other route of administration to the systemic circulation Platz, 1992, Byron andPatton, 1994).…”
Section: Deliverymentioning
confidence: 99%
“…Aerosolized Antibiotic Therapy Barach 128 Well-controlled placebo trials or comparisons with systemic therapy have not been done due to ethical considerations of withholding therapy in patients. However, trials of aerosolized polymyxin for prophylaxis against gram-negative pneumonia in seriously ill patients have failed.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…However, trials of aerosolized polymyxin for prophylaxis against gram-negative pneumonia in seriously ill patients have failed. 128 When used continuously, the aerosol appears to increase the development of polymyxin-resistant organisms. 128 Aerosolized gentamicin and carbenicillin have been used in PA pneumonia without clear evidence of improved therapeutic effect.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation